The impact of differentiated task-based instruction via heeding learning styles on EFL learners' feasible proficiency gains - Alavinia, Parviz; Sadeghi, Tahereh (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Around 3 decades of scrupulous work, theorizing and experimentation in the realm of differentiated instruction (DI) has provided it with an unprecedented and ever-increasing splendor. Yet, the fuzziness, in terms of methodological and practical concerns, with which the theory was once characterised, has not yet completely been tackled. The present study is, hence, an attempt to partly diminish this aura of blurredness and imprecision surrounding DI, particularly for novice practitioners by implementing and running a differentially instructed class. The study sets out to investigate the impact of DI on EFL learners’ proficiency. A small sample size of academic freshmen (totaling 60, out of which only 47 remained to the end of the study), was selected through convenience sampling and rearranged under distinct groups based on learning styles using Chislett and Chapman’s (2005) learning style inventory. The results reveal, contrary to the study postulations, no significant proficiency differences resulting from differentiated task-based instruction between the experimental and control groups.